Secrets of Dripping Fang. Book one, The Onts [compact disc, unabridged] - Greenburg, Dan (Greenburg, Dan. Secrets of Dripping Fang, 2007)
Ten-year-old orphan twins Wally and Cheyenne Shluffmuffin have a hard time at Cincinnati's Jolly Days Orphanage, but things get much worse when the Mandible sisters offer to share their home in the Dripping Fang Forest.